Effect of Salt Stress on Growth and Mineral Elements Concentrations in Shoot and Root of Maize Plant - Süleyman Taban (Journal of Agricultural Sciences)
Effect of soil applied NaCI on shoot and root growth and Na, Cl, N. P. K, Ca, Mg, Fe, Zn and Mn concentrations in shoot and root of the maize plant (Zea mays L. cv: RX 947) vvas investigated. The experiment vvas arranged in a completely randomized design with four replications under the greenhouse condition The experimental soil vvas sailnized with NaCI at the rates of 0, 15, 30, 45 and 60 mM kg’1 NaCI. Shoot and root growth of the maize plants vvas inhibited by salinity. Increasing amount of NaCI applicatlon decreased the dry vveight of shoot and root. Na, Cl and P concentrations in the shopt and root increased with Increasing amount of NaCI. VVhile applied NaCI caused to decrease N. Ca and Fe concentrations in the shoot. to increase N Ca. Mg and Fe concentrations in the rooL Zn.and Mn concentrations in the shoot and root vvere increased due to Increasing amount of NaCI. Na, P, Mg, Fe, Zn and Mri accumulated in the root İn according vvith applied NaCI.